2019
DOI: 10.1002/smll.201901073
|View full text |Cite|
|
Sign up to set email alerts
|

Key Role of Microtubule and Its Acetylation in a Zinc Oxide Nanoparticle–Mediated Lysosome–Autophagy System

Abstract: Autophagy is a biological process that has attracted considerable attention as a target for novel therapeutics. Recently, nanomaterials (NMs) have been reported to modulate autophagy, which makes them potential agents for the treatment of autophagy‐related diseases. In this study, zinc oxide nanoparticles (ZNPs) are utilized to evaluate NM‐induced autophagy and debate the mechanisms involved. It is found that ZNPs undergo pH‐dependent ion shedding and that intracellular zinc ions (Zn2+) play a crucial role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…[102][103][104][105][106][107][108][109][110][111][112] Metal nanoparticles including alpha-aluminum oxide, [119] copper, [120,121] cobalt chromium-molybdenum, [122] cuprous oxide, [124] iron oxide, [125,126] cobalt and chromium, [123] silica, [127][128][129][130]133] silver, [131,132] zinc oxide, [134,135] upconversion, [136,137,147] and titanium dioxide [90,138] are intracellularly trafficked through endocytosis or another uptake pathway and processed through the autophagy pathway. [90,[119][120][121][122][123][124][125][126][127][128][129][130][131][132]…”
Section: Selective Autophagy Of Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…[102][103][104][105][106][107][108][109][110][111][112] Metal nanoparticles including alpha-aluminum oxide, [119] copper, [120,121] cobalt chromium-molybdenum, [122] cuprous oxide, [124] iron oxide, [125,126] cobalt and chromium, [123] silica, [127][128][129][130]133] silver, [131,132] zinc oxide, [134,135] upconversion, [136,137,147] and titanium dioxide [90,138] are intracellularly trafficked through endocytosis or another uptake pathway and processed through the autophagy pathway. [90,[119][120][121][122][123][124][125][126][127][128][129][130][131][132]…”
Section: Selective Autophagy Of Nanoparticlesmentioning
confidence: 99%
“…Examples of organic nanocarriers are polymeric nanoparticles, [102,105,106,[159][160][161] nanoliposomes, [162] and nanogels [111] and those of inorganic nanocarriers are carbon [163,164] and metal nanoparticles. [129,147,165] Drugs such as atazanavir, [160,161] bafilomycin A1, [147] brefeldin A, [166] ceramide, [162] cisplatin, [164,167] docetaxel, [102,105,106] doxorubicin, [111] fumagillin, [163] paclitaxel, [129,159,168] small molecule inhibitor 9 (SMI#9), [165] temozolomide, [159] and vinblastine [162] can be loaded onto various nanocarriers. These nanodrugs are intracellularly trafficked and processed through the autophagy pathway in various cell types, as shown in Table 2.…”
Section: Selective Autophagy Of Nanodrugs In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Upconversion NPs encapsulating chlorin e6 effectively enhance the generation of ROS and subsequently, stimulate autophagy through PI3K/Akt/mTOR signaling pathway, resulting in down-regulation of pro-inflammatory factors (IL-12, TNF-α and iNOS) production [12]. Taking everything into account, NPs are able to regulate autophagy and this potential can be promisingly used in biomedical applications [334]. However, these nanoparticles could also trigger other organ toxicity tightly related with autophagy.…”
Section: Nanocarriers As Autophagy Modulator: Challenging To Desimentioning
confidence: 99%
“…Finally, autolysosomes are disassembled, providing nutrition and energy for cells in response to many severe cellular conditions. 4,5 Recent studies have shown that autophagy dysfunction is associated with tumors, 6 neurodegenerative diseases, 7 cardiovascular diseases 8 and infections. 9 Compared to other pathophysiology, the role of autophagy in cancer is more complicated because autophagy plays a "doubleedged sword" role in various types of cancer, 10,11 mediating carcinogenesis or anticancer effects.…”
Section: Introductionmentioning
confidence: 99%